Clinical validation of the nursing diagnosis “Risk for delayed child development”* - Melo, Nádia Proença de; Souza, Juliana Martins de; Cordeiro, Samara Macedo; Veríssimo, Maria de La Ó Ramallo (Revista da Escola de Enfermagem da USP, 2022)
Objective: To validate clinically the risk factors of the nursing diagnosis “Risk for delayed child development”. Method: Cross-sectional quantitative study carried out in a specialty outpatient clinic and in family health units with 124 children. The data was collected through interviews with the children’s guardians to investigate the risk factors for delay in child development. Results: The tested risk factors affected 108 of the evaluated children (87.1%). In the accuracy tests, most specificity values were above 80% and sensitivity values were lower than 30%. Most risk factors had odds ratio >1, three of which were noteworthy: genetic disorder (OR = 38, p < 0.05) and congenital disorder (OR = 4.4, p < 0.05), among child-related aspects, and impaired cognitive development in parents (OR = 27, p < 0.05), among caregiver-related aspects. Conclusion: The study contributed to a refined diagnostic accuracy, identifying potential associated factors of the evaluated diagnosis.